Spatial Variations of Prokaryotic Communities in Surface Water from India Ocean to Chinese Marginal Seas and their Underlining Environmental Determinants - Zheng, Xiaowei; Dai, Xin; Huang, Li (Frontiers in Marine Science, 2016)
To illustrate the biogeographic patterns of prokaryotic communities in surface sea water, 24 samples were systematically collected across a large distance from Indian Ocean to Chinese marginal seas, with an average distance of 453 km between two adjacent stations. A total of 841,364 quality reads was produced by the high throughput DNA sequencing of the 16S rRNA genes. Phylogenetic analysis showed that Proteobacteria were predominant in all samples, with Alphaproteobacteria and Gammaproteobacteria being the two most abundant components. Cyanobacteria represented the second largest fraction of the total quality reads, and mainly included Prochlorococcus and Synechococcus. The semi-closed marginal seas, including South China Sea (SCS) and nearby regions, exhibited a transition in community composition between oceanic and coastal seas, based on the distribution patterns of Prochlorococcus and Synechococcus as well as a non-metric multidimensional scaling (NMDS) analysis. Distinct clusters of prokaryotes from coastal and open seas, and from different water masses in Indian Ocean were obtained by Bray-Curtis dissimilarity analysis at the OTU level, revealing a clear spatial heterogeneity. The major environmental factors correlated with the community variation in this broad scale were identified as salinity, temperature and geographic distance. Community comparison among regions shows that anthropogenic contamination is another dominant factor in shaping the biogeographic patterns of the microorganisms. These results suggest that environmental factors involved in complex interactions between land and sea act synergistically in driving spatial variations in coastal areas.